2021
DOI: 10.1177/23998083211007866
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neighborhood land use structure and the spatiotemporal pattern of PM2.5 at the microscale: Evidence from the central area of Guangzhou, China

Abstract: Fine particulate matter (PM2.5) is harmful to human health. Although the relationship between urban land use and PM2.5 has been studied in recent years, there has been little consideration of the relationship between land use structure and PM2.5 spatiotemporal patterns at the microscale. Based on mobile monitoring PM2.5 data and point of interest data, this paper explored their relationship with a classification and regression tree model. The results showed that PM2.5 exhibits spatiotemporal heterogeneity at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…For example, population agglomeration and open space may substantially impact particulate matter. Because the heavier traffic volume resulting from the population agglomeration increases PM 2.5 in the atmosphere, the more the open space exists, the better air ventilation (Chun et al, 2022; Song et al, 2021). Additionally, this study has investigated the impact of urban form factors on the particulate matter concentration within a 1 km buffer from each station, but the buffer distance cannot be universalized to all situations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, population agglomeration and open space may substantially impact particulate matter. Because the heavier traffic volume resulting from the population agglomeration increases PM 2.5 in the atmosphere, the more the open space exists, the better air ventilation (Chun et al, 2022; Song et al, 2021). Additionally, this study has investigated the impact of urban form factors on the particulate matter concentration within a 1 km buffer from each station, but the buffer distance cannot be universalized to all situations.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, high traffic volumes in industrial districts during weekdays contribute to elevated levels of air pollution; in addition, their RF model obtained the highest R 2 value to explain these interrelationships. Similarly, Song et al (2021) recently found that land-use structure could help predict the PM2.5 patterns in Guangzhou, China. They use PM2.5 information collected at monitoring stations located along express highways.…”
Section: Literature Reviewmentioning
confidence: 89%
“…As tourism rapidly develops, localized space, as a core element of tourism development, has shifted the focus of research on destination personality towards process interpretation and spatial significance analysis. Only through a comprehensive analysis framework of "people-time-space" unity can the full meaning of 'localized space' be constructed [28][29][30]. From a historical evolution perspective, the analysis of tourism destination personality, based on the context of "dynamic territorial systems", emphasizes the analysis of the internal cultural core composition and spatial structure evolution process in the formation of the tourism destination territorial system and distinctive pattern.…”
Section: Literature Review and Theoretical Framework 21 Study On The ...mentioning
confidence: 99%